The influence of fasting and cortisol upon arginosuccinate synthetase, arginosuccinase and arginase levels in guinea pig liver (Revista Española de Fisiología, 1980)
The influence of fasting and cortisol treatment on the levels of arginosuccinate synthetase (E.C.6.3.4.5.), ARGINOSUCCINASe (E.C.4.3.2.1) and arginase (C.E.3.5.3.1) from guinea pig liver has been investigated.The results show a general increase in the levels of the mentioned enzymes, with specific enzyme synthesis for fasting, and unspecific for cortisol treatment.